President of Everything: Mothering during COVID - Edith Gnanadass; Alison Happel-Parkins; Katharina Azim; Keishana L Barnes; Mary Hilgeman Neal (Adult Education Research Conference, 2023)
This roundtable explores narrative data collected from seven women in the U.S. Midsouth about their mothering experiences during COVID-19. The focus will be on their socio-emotional and informal learning.
Keywords: Mothering during the pandemic; informal learning; socio-emotional learning; adult learning and COVID